Effect of fluidised bed drying on ginsenoside content in hairy root cultures of Panax ginseng C.A. Meyer - James Setiabudi; Komang Mega Oka Sri Bintang; Stella Stacia Gani; Pissa Christanti; Evanie Noer Putri; Se Chan Kang; Johan Sukweenadhi (Universitas Gadjah Mada, 2023)
Korean Ginseng (Panax ginseng C.A. Meyer) is a high‐value herb with many pharmacological benefits due to its primary active compound, ginsenosides. The most ginsenosides are known to be thermolabile and susceptible to degradation at high‐temperature processing. Our previous studies revealed that the optimum parameters related to the P. ginseng tissue culture protocol, particularly for hairy root propagation of Cultured Roots of Mountain Ginseng (CRMG)‐88, was using a lab‐scale bioreactor. The next stage involves screening for a suitable post‐harvest treatment, i.e., drying, will be production of the best quality ginsenoside content. This study therefore aimed to examine the ginsenoside content by using a fluidised bed dryer (FBD) on the ginseng roots. Our results showed that FBD produced a significantly higher of total ginsenoside content (5.386 ± 1.167%), compared to control (3.750 ± 0.641%). FBD‐dried CRMG‐88 also appeared lighter in colour and more voluminous with a Loss on Drying (LOD) of 6.448 ± 1.900%. This study concluded that fluidised bed drying is superior in retaining ginsenoside content and has the potential for large‐scale application.